2009
DOI: 10.1002/syn.20618
|View full text |Cite
|
Sign up to set email alerts
|

Asenapine exerts distinctive regional effects on ionotropic glutamate receptor subtypes in rat brain

Abstract: Asenapine, a new pyschopharmacologic agent being developed for the treatment of schizophrenia and bipolar disorder, has a unique human receptor binding signature with strong affinity for dopaminergic, alpha-adrenergic, and, in particular, serotonergic receptors raising the possibility of interactions with glutamatergic receptors. Changes in ionotropic glutamate (Glu) N-methyl-D-aspartic acid (NMDA) receptors and 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propionic acid (AMPA) receptors in rat forebrain region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…In this regard, the effects of asenapine on muscarinic receptors are similar to its effects on ionotropic glutamate receptors. Asenapine also alters 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propionic acid (AMPA) and N-methyl-D-aspartic acid (NMDA) receptor binding without having demonstrable affinity for these receptors (Tarazi et al 2009). Given the diverse actions of cortical and hippocampal muscarinic receptor subtypes and the inability to specifically ascertain the receptor subtypes altered by asenapine in this study, the functional implications of these changes at the neuronal level require further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In this regard, the effects of asenapine on muscarinic receptors are similar to its effects on ionotropic glutamate receptors. Asenapine also alters 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propionic acid (AMPA) and N-methyl-D-aspartic acid (NMDA) receptor binding without having demonstrable affinity for these receptors (Tarazi et al 2009). Given the diverse actions of cortical and hippocampal muscarinic receptor subtypes and the inability to specifically ascertain the receptor subtypes altered by asenapine in this study, the functional implications of these changes at the neuronal level require further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…The modulation of these receptor systems by asenapine, together with effects on dopamine, serotonin, and ionotropic glutamate receptor subtypes (Tarazi et al 2008(Tarazi et al , 2009) may contribute to its efficacy in treating multiple symptom domains in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in studies with monkeys, asenapine produced substantial improvement in executive functions which were maintained across a period of long-term dosing. 46 Further studies in rat brain have indicated that chronic treatment with asenapine exerts regional and dose-dependent effects on inotropic glutamate receptors, 47 thus another potential mechanism for its effectiveness in schizophrenia.…”
Section: Pharmacology and Mode Of Actionmentioning
confidence: 99%